The Effect of Gender Diversity and Slack Resources on Corporate Social Responsibility Disclosure - Rohmah, Neng Siti; Nurfauziah, Farah Latifah; Suharti, Sri (GOVERNORS, 2022)
The purpose of this study was to determine the effect of gender diversity and slack resources on the corporate social responsibility disclosure. This study uses secondary data obtained from the annual report on the IDX. The population in this study were all mining companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 and sampling using the purposive sampling method and obtained a sample of 14 companies. The technique used in this research is robust regression analysis using Eviews 12. The research method used is a quantitative method with the dependent variable, namely corporate social responsibility disclosure and the independent variables, namely gender diversity and slack resources. The results of this study indicate that gender diversity has an effect on corporate social responsibility disclosure with a result of 0.004 less than 0.05 while slack resources has no effect on corporate social responsibility disclosure with a result of 0.146 greater than 0.05 in mining companies. Simultaneous results with F of 0.000365 can be seen that the variables of gender diversity and slack resources have an effect on coporate social responsibility disclosure.